A kind of preparation method of polyester staple fiber
By depositing titanium dioxide film on the surface of coconut fiber and using composite functional additives, combined with melt spinning technology, polyester staple fibers with multi-color, warm, dry, comfortable and antibacterial properties were prepared, which solved the color limitations of coconut fiber fabrics in the prior art and Problem of insufficient performance.
Patent Information
- Application Number
- CN202211441124.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-11-17
AI Technical Summary
In the prior art, the color of coconut fiber is used in fabric preparation limits its use range, and there is a lack of a polyester staple fiber preparation method that is both warm, dry, comfortable and antibacterial.
Polyester staple fibers are prepared by preparing coconut fiber ultrafine powder and depositing titanium dioxide film on its surface, combined with composite functional additives such as silica, germanium oxide and surface-modified aluminum-doped zinc oxide powder, polyester staple fibers are prepared by melt spinning process. Adjust the thickness of the titanium dioxide film for a variety of colors and excellent warmth.
The prepared polyester staple fiber has a variety of color choices, good warmth, fracture strength and moisture rebate, ensuring dryness, comfort and antibacteriality, expanding its application range.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spinning, and in particular to a method for preparing polyester staple fibers. Background Art
[0002] Polyester staple fiber is made of polyester (polyethylene terephthalate, abbreviated as PET, which is polymerized by PTA and MEG, and then spun into tows and cut into fibers. PET is in the shape of rice grains or sheets, with various varieties and colors. The main component of many beverage bottles we usually come into contact with is polyester. Slicing it, generally through the two main processes of pre-spinning and post-spinning, can produce polyester staple fiber. According to different needs, it can be cut into polyester staple fibers of different specifications in post-spinning.
[0003] A Chinese patent with authorization announcement number CN109252242B discloses a polyester staple fiber and a preparation method thereof. The composite functional additive is designed to be a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, and the above mass ratio is designed so that the polyester staple fiber can obtain good far-infrared emission function and thus obtain good thermal insulation performance, and the thermal insulation performance can be further improved by combining with the design of powder particle size.
[0004] Coconut charcoal fiber is a new type of environmentally friendly material. When the coconut pulp and coconut water are taken away and processed into food, the coarse coconut shell waste will cause great pressure on environmental remediation. However, people collect the waste coconut shells and make them recyclable. Through soaking, beating, filtering residues, and drying, we can finally obtain the fiber of coconut shells: coconut fiber. Then, the coconut fiber is heated to 1200℃ and carbonized at high temperature to obtain coconut charcoal with excellent properties. The molecular formula of coconut charcoal is hexagonal, the carbon is inseparable, the relative density is large, and there are many pores. The total area of the microporous plate is more than 4 times that of bamboo charcoal, and it has a strong adsorption function.
[0005] In the prior art, although there are publicized recipes for using coconut charcoal fiber as fabrics, for example, a Chinese patent with authorization announcement number CN106435944B discloses a new type of antibacterial fabric, and its specific preparation method is to add pearl fiber; wool fiber; corn protein fiber; modal fiber; coconut charcoal fiber; tea fiber; antibacterial finishing agent at 40-45°C, add dispersant, binder, softener, add 100-120 parts of water, mix and stir evenly, and then air-dry to form; then the mixture is subjected to cleaning, opening, drawing, coarse yarn, and spun yarn to form functional yarn lines; and then the functional yarn lines are knitted or woven into cloth. It can be seen that in the prior art, carbon fiber is mixed with other fiber materials and then made into yarn according to the traditional spinning process of cleaning, opening, drawing, roving and spinning, and is not combined with the melt spinning technology of polyester fiber. Since the color of coconut charcoal fiber itself is dark black and its dyeing performance is poor, the yarn or fabric using coconut charcoal fiber on the market is gray-black in color, thus limiting the scope of use.
[0006] Based on the above-mentioned prior art, there is an urgent need to provide a method for preparing polyester staple fibers, so that the prepared polyester staple fibers have the advantages of warmth, dryness, comfort and antibacterial properties, and can also have more diverse colors. Summary of the invention
[0007] The technical problem to be solved by the present invention is: it is urgent to provide a method for preparing polyester staple fibers, so that the prepared polyester staple fibers have the advantages of warmth retention, dryness, comfort and antibacterial properties, and can also have more diverse colors.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0009] A method for preparing polyester staple fibers comprises the following steps:
[0010] Step 1: preparing coconut charcoal fiber ultrafine powder;
[0011] Step 2: Place the coconut charcoal fiber ultrafine powder into the reaction vessel of the atomic deposition equipment at a reaction temperature of 100-110°C;
[0012] Step 3: introducing titanium tetraisopropoxide vapor into a continuously stirred reaction vessel for 8 seconds, purging with nitrogen for 20 seconds, and then intermittently introducing deionized water into the reaction vessel for 8 seconds, purging with nitrogen for 20 seconds;
[0013] Repeat the above step 3 for n times, where n is any value between 5 and 10000, to deposit a titanium dioxide film on the surface of the coconut charcoal fiber ultrafine powder;
[0014] Step 4: 300 parts by weight of terephthalic acid and 50 parts by weight of an organic solvent (ethanol or isopropanol) are mixed at 50-60° C.; then the temperature is raised to 150-160° C. for esterification reaction, and the reaction time is 10-15 minutes;
[0015] Step 5: Add 60-0.005n parts by weight of the carbon fiber ultrafine powder with a titanium dioxide film deposited on the surface obtained in step 3 to the product after the esterification reaction; then add 8-10 parts by weight of dimethyl propanediol, 5-10 parts by weight of 2,5-dimethyl-2,5-hexyne diol, 5-15 parts by weight of 2-butene-1,4-di-n-butyl ester, 5-10 parts by weight of di(hexane-1,6-diol)titanium, 5-10 parts by weight of composite functional additives, 100 parts by weight of terephthalic acid and 50 parts by weight of ethylene glycol ester, and then heat to 200-250° C. and simmer under vacuum conditions of 200-300 Pa. The reaction was carried out for 10-15 minutes to carry out a first polymerization reaction; then 90-0.007n parts by weight of the carbon fiber ultrafine powder with a titanium dioxide film deposited on the surface obtained in step 3 was added, and then the mixture was reacted for 5-10 minutes at 230-260° C. and 250-350 Pa vacuum conditions to carry out a second polymerization reaction to obtain a copolyester melt; the composite functional additive is a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, and the mass ratios of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder are 1:(2-4):1:(2-4) in sequence;
[0016] Step 6: melt-spinning the copolyester melt to obtain a melt, wherein the spinning temperature is 270-290° C.;
[0017] Step 7: Extruding the melt through a special-shaped spinneret to form a melt stream, and cooling the stream, wherein the spinneret micropores are in the shape of a gear;
[0018] Step 8: The melt stream extruded and cooled from the spinneret is guided, heat-set and wound to obtain polyester staple fibers.
[0019] Preferably, in the above-mentioned method for preparing polyester staple fibers, the step 1 specifically comprises: heating the fiber of coconut shell to 1200° C., carbonizing it under a vacuum environment, and ultrafinely grinding the carbonized fiber to obtain coconut charcoal fiber ultrafine powder.
[0020] Preferably, in the above-mentioned method for preparing polyester staple fibers, the particle sizes of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder are 10-30 microns.
[0021] Preferably, in the above-mentioned method for preparing polyester staple fibers, the number of gear-shaped teeth of the spinning microholes of the spinneret is 6-8.
[0022] Preferably, in the above-mentioned method for preparing polyester staple fibers, the diameter of the gear-shaped spinning microholes of the spinneret is 0.4-0.6 mm, and the gear-shaped tooth height is 0.05-0.1 mm.
[0023] Preferably, in the above-mentioned method for preparing polyester staple fibers, step 8 is specifically as follows: the filament bundle after oiling and bundling by the nozzle is input into the lower wire guide disk at a speed of 3105-3610 m / min, and then enters the hot wire guide roller with a speed of 3105-3610 m / min and a temperature of 120-135°C for heat setting; and is wound and formed at a winding speed of 3100-3600 m / min to obtain the polyester staple fibers.
[0024] Preferably, in the preparation method of the coconut charcoal polyester fiber, the cooling in step 7 is specifically: using a side-blowing cooling process to solidify into filaments; the conditions of the side-blowing cooling process are: the side-blowing speed is 0.30m / s-0.50m / s, the side-blowing temperature is 18°C, and the side-blowing humidity is 75%.
[0025] The present invention also protects the polyester staple fiber product obtained by the preparation method of the polyester staple fiber.
[0026] The beneficial effects of the present invention are:
[0027] The method of preparing coconut charcoal fiber ultrafine powder and depositing titanium tetraisopropoxide on the surface of coconut charcoal fiber ultrafine powder makes titanium dioxide film uniformly deposited on the surface of coconut charcoal fiber ultrafine powder. This is to utilize the oxygen-containing functional groups such as -OH and -COOH on the surface of coconut charcoal fiber to effectively start the growth characteristics of titanium dioxide film. First, titanium tetraisopropoxide is introduced to form -OCH(CH3)2 on the surface of coconut charcoal fiber through the self-limiting chemical reaction of the active groups of the oxygen-containing functional groups on the surface of coconut charcoal fiber, and H2O is introduced to react with -OCH(CH3)2 to form a single-layer titanium dioxide film and exposed -OH. After each step, the remaining substances are blown away by nitrogen. The required titanium dioxide film thickness can be adjusted by repeating the number of cycles;
[0028] By adjusting the thickness of the titanium dioxide film, the surface of the coconut charcoal fiber can present different colors. In the melt extrusion spinning process, by sequentially adding a specific amount of coconut charcoal fiber powder with a titanium dioxide film during the secondary polymerization reaction, the amount of coconut charcoal fiber powder added during the second polymerization reaction is greater than the amount of coconut charcoal fiber powder added during the first polymerization reaction, so that the coconut charcoal fiber powder and the polymer can be more evenly mixed, so that when the melt extrusion forms a melt stream, the coconut charcoal fiber can be evenly distributed; in each polymerization reaction, the amount of coconut charcoal fiber added is appropriately adjusted according to the number of titanium dioxide deposition times of the coconut charcoal fiber, that is, the thickness of the film, so that the coconut charcoal fiber itself maintains a stable amount of addition during the polymerization reaction.
[0029] The composite functional additive is designed to be a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, and the above mass ratio is designed, so that the polyester staple fiber can obtain good far-infrared emission function and thus obtain good thermal insulation performance, and can be combined with the design of powder particle size to further improve its thermal insulation performance; the added dimethyl propanediol, 2,5-dimethyl-2,5-hexyne diol, 2-butene-1,4-di-n-butyl ester, and di(hexane-1,6-diol) titanium can be used as regulators to control the molecular structure of the polymer obtained after the polymerization reaction, and can be used in combination with the above composite functional additives to enable the prepared polyester staple fiber to have good thermal insulation performance, breaking strength and regain; and the mineral content in coconut charcoal is varied. Coconut charcoal can absorb and emit far infrared rays with a wavelength of 4 to 14 μm, thereby stimulating the formation of negative ions that are beneficial to the body. In addition, since the above-mentioned polyester staple fiber and other raw materials have thermal insulation properties, combined with coconut charcoal fiber, a porous and water-permeable surface layer can be produced on the fiber surface, which can dissolve skin sweat and quickly diffuse and evaporate, ensuring dryness and comfort while keeping warm and avoiding bacterial growth.
[0030] Due to the different thickness of titanium dioxide deposited on the surface of coconut charcoal fiber, different colors are presented. For example, when n is 200, when the thickness of titanium dioxide deposited on the surface of coconut charcoal fiber is 20nm, the surface is light yellow. For example, when n is 400, when the thickness of titanium dioxide deposited on the surface of coconut charcoal fiber is 40nm, the surface is purple-red. For example, when n is 600, when the thickness of titanium dioxide deposited on the surface of coconut charcoal fiber is 60nm, the surface color of coconut charcoal fiber is blue-purple. The color selection of coconut charcoal fiber can be selected according to the needs of subsequent polyester staple fiber or subsequent cloth dyeing, so that the polyester staple fiber prepared above can meet the processing needs of different colors. DETAILED DESCRIPTION
[0031] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes.
[0032] Example 1
[0033] A method for preparing polyester staple fibers comprises the following steps:
[0034] Step 1: heating the coconut shell fiber to 1200° C., carbonizing it under vacuum, and ultrafine grinding the carbonized fiber to obtain coconut charcoal fiber ultrafine powder, wherein the particle size of the coconut charcoal fiber ultrafine powder is 15 μm;
[0035] Step 2: Place the coconut charcoal fiber ultrafine powder into the reaction vessel of the atomic deposition equipment at a reaction temperature of 105°C;
[0036] Step 3: introducing titanium tetraisopropoxide vapor into a continuously stirred reaction vessel for 8 seconds, purging with nitrogen for 20 seconds, and then intermittently introducing deionized water into the reaction vessel for 8 seconds, purging with nitrogen for 20 seconds;
[0037] Repeat step 3 for 200 times to deposit a 20 nm thick titanium dioxide film on the surface of the coconut charcoal fiber ultrafine powder, so that the surface of the coconut charcoal fiber appears light yellow;
[0038] Step 4: 300 kg of terephthalic acid and 50 kg of an organic solvent (ethanol or isopropanol) are mixed at 50-60° C.; then the temperature is raised to 155° C. for esterification reaction, and the reaction time is 102 min;
[0039] Step 5: Add 59.9 kg of carbon fiber ultrafine powder with titanium dioxide film deposited on the surface obtained in step 3 to the product after the esterification reaction; then add 9 kg of dimethyl propanediol, 7 kg of 2,5-dimethyl-2,5-hexyne diol, 5-15 kg of 2-butene-1,4-di-n-butyl ester, 7 kg of di(hexane-1,6-diol) titanium, 7 kg of composite functional additives, 100 kg of terephthalic acid and 50 kg of ethylene glycol ester, then heat to 220° C., react under 250 Pa vacuum conditions for 12 min to carry out the first polymerization reaction; then add 8 9.86 kg of the carbon fiber ultrafine powder with a titanium dioxide film deposited on the surface obtained in step 3, reacting for 7 minutes at 245° C. and 300 Pa vacuum conditions, performing a second polymerization reaction, and obtaining a copolyester melt; the composite functional additive is a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, the mass ratio of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 1:3:1:3, and the particle size of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 20 microns;
[0040] Step 6: melt-spinning the copolyester melt to obtain a melt, wherein the spinning temperature is 280° C.;
[0041] Step 7: extruding the melt through a special-shaped spinneret to form a melt stream, and cooling the melt stream, wherein the spinneret has a spinning micropore in the shape of a gear and has 7 teeth; the cooling comprises: solidifying the melt stream into a filament by a side-blowing cooling process; the side-blowing cooling process comprises: a side-blowing speed of 0.30 m / s-0.50 m / s, a side-blowing temperature of 18° C., and a side-blowing humidity of 75%;
[0042] Step 8: The melt stream extruded and cooled from the spinneret is subjected to wire guiding, heat setting and winding. Specifically, the filament bundle after oiling and bundling by the nozzle is input into the lower wire guide disk at a speed of 3410 m / min, and then enters the hot wire guide roller at a speed of 3410 m / min and a temperature of 130°C for heat setting; the winding is carried out at a winding speed of 3400 m / min to obtain the polyester staple fiber.
[0043] Example 2
[0044] A method for preparing polyester staple fibers comprises the following steps:
[0045] Step 1: heating the fiber of coconut shell to 1200° C., carbonizing it under vacuum, and ultrafine grinding the carbonized fiber to obtain ultrafine coconut charcoal fiber powder, wherein the particle size of the ultrafine coconut charcoal fiber powder is 10 μm;
[0046] Step 2: Place the coconut charcoal fiber ultrafine powder into the reaction vessel of the atomic deposition equipment at a reaction temperature of 100°C;
[0047] Step 3: introducing titanium tetraisopropoxide vapor into a continuously stirred reaction vessel for 8 seconds, purging with nitrogen for 20 seconds, and then intermittently introducing deionized water into the reaction vessel for 8 seconds, purging with nitrogen for 20 seconds;
[0048] Repeat step 3 for 400 times to deposit a 40nm titanium dioxide film on the surface of the coconut charcoal fiber ultrafine powder, making the surface of the coconut charcoal fiber appear purple-red;
[0049] Step 4: 300 kg of terephthalic acid and 50 kg of an organic solvent (ethanol or isopropanol) are mixed at 50° C., and then the temperature is raised to 150° C. for esterification reaction, and the reaction time is 10 min;
[0050] Step 5: Add 59.8 kg of carbon fiber ultrafine powder with titanium dioxide film deposited on the surface obtained in step 3 to the product after the esterification reaction; then add 8 kg of dimethyl propanediol, 5 kg of 2,5-dimethyl-2,5-hexyne diol, 5 kg of 2-butene-1,4-di-n-butyl ester, 5 kg of di(hexane-1,6-diol) titanium, 5 kg of composite functional additives, 100 kg of terephthalic acid and 50 kg of ethylene glycol ester, then heat to 200°C, react under 200 Pa vacuum condition for 10 min, and carry out the first polymerization reaction; then add 89. ... propanediol, 5 kg of 2-butene-1,4-di-n-butyl ester, 5 kg of di(hexane-1,6-diol) titanium, 5 kg of composite functional additives, 100 kg of terephthalic acid and 50 kg of ethylene glycol ester, then heat to 200°C, react under 200 Pa vacuum condition for 10 min, and carry out the first polymerization reaction; then add 89.8 kg of dimethyl propanediol, 5 kg of 2,5-dimethyl propanediol, 5 kg of 2-butene- 72kg of the carbon fiber ultrafine powder with a titanium dioxide film deposited on the surface obtained in step 3, reacting for 5 minutes at 230°C and 250Pa vacuum conditions, performing a second polymerization reaction, and obtaining a copolyester melt; the composite functional additive is a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, the mass ratio of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 1:2:1:2, and the particle size of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 10 microns;
[0051] Step 6: melt-spinning the copolyester melt to obtain a melt, wherein the spinning temperature is 270° C.;
[0052] Step 7: Extruding the melt through a special-shaped spinneret to form a melt stream, and cooling the melt stream, wherein the spinneret has a spinning micropore in the shape of a gear and has 6 teeth; the cooling comprises: solidifying the melt stream into a filament by a side-blowing cooling process; the side-blowing cooling process comprises: a side-blowing speed of 0.30 m / s-0.50 m / s, a side-blowing temperature of 18° C., and a side-blowing humidity of 75%;
[0053] Step 8: The melt stream extruded and cooled from the spinneret is subjected to wire guiding, heat setting and winding. Specifically, the filament bundle after oiling and bundling by the nozzle is input into the lower wire guide disk at a speed of 3105 m / min, and then enters the hot wire guide roller at a speed of 3105 m / min and a temperature of 120°C for heat setting; the winding is carried out at a winding speed of 3100 m / min to obtain the polyester staple fiber; and the polyester staple fiber is obtained.
[0054] Example 3
[0055] A method for preparing polyester staple fibers comprises the following steps:
[0056] Step 1: heating the fiber of coconut shell to 1200° C., carbonizing it under vacuum, and ultrafine grinding the carbonized fiber to obtain ultrafine coconut charcoal fiber powder, wherein the particle size of the ultrafine coconut charcoal fiber powder is 20 μm;
[0057] Step 2: Place the coconut charcoal fiber ultrafine powder into the reaction vessel of the atomic deposition equipment at a reaction temperature of 100-110°C;
[0058] Step 3: introducing titanium tetraisopropoxide vapor into a continuously stirred reaction vessel for 8 seconds, purging with nitrogen for 20 seconds, and then intermittently introducing deionized water into the reaction vessel for 8 seconds, purging with nitrogen for 20 seconds;
[0059] Repeat the above step 3 for 600 times to deposit a 60nm titanium dioxide film on the surface of the coconut charcoal fiber ultrafine powder, making the surface of the coconut charcoal fiber appear blue-purple;
[0060] Step 4: 300 kg of terephthalic acid and 50 kg of an organic solvent (ethanol or isopropanol) are mixed at 60° C., and then the temperature is raised to 160° C. for esterification reaction, and the reaction time is 15 minutes;
[0061] Step 5: Add 59.7 kg of carbon fiber ultrafine powder with titanium dioxide film deposited on the surface obtained in step 3 to the product after the esterification reaction; then add 10 kg of dimethyl propanediol, 10 kg of 2,5-dimethyl-2,5-hexyne diol, 15 kg of 2-butene-1,4-di-n-butyl ester, 10 kg of di(hexane-1,6-diol) titanium, 10 kg of composite functional additives, 100 kg of terephthalic acid and 50 kg of ethylene glycol ester, then heat to 250° C., react under 300 Pa vacuum conditions for 15 min to carry out the first polymerization reaction; then add 8 9.58 kg of the carbon fiber ultrafine powder with a titanium dioxide film deposited on the surface obtained in step 3, reacting for 10 minutes at 260° C. and 350 Pa vacuum conditions, performing a second polymerization reaction, and obtaining a copolyester melt; the composite functional additive is a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, the mass ratio of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 1:4:1:4, and the particle size of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 30 microns;
[0062] Step 6: melt-spinning the copolyester melt to obtain a melt, wherein the spinning temperature is 290° C.;
[0063] Step 7: Extruding the melt through a special-shaped spinneret to form a melt stream, and cooling the melt stream, wherein the spinneret has a spinning micropore in the shape of a gear and has 8 teeth; the cooling comprises: solidifying the melt stream into a filament by a side-blowing cooling process; the side-blowing cooling process comprises: a side-blowing speed of 0.30 m / s-0.50 m / s, a side-blowing temperature of 18° C., and a side-blowing humidity of 75%;
[0064] Step 8: The melt stream extruded and cooled from the spinneret is subjected to wire guiding, heat setting and winding. Specifically, the filament bundle after oiling and bundling by the nozzle is input into the lower wire guide disk at a speed of 3610 m / min, and then enters the hot wire guide roller at a speed of 3610 m / min and a temperature of 135°C for heat setting; the winding is carried out at a winding speed of 3600 m / min to obtain the polyester staple fiber.
[0065] Performance Test:
[0066] 1. According to GB / T6503-2008, the breaking strength and moisture regain of the polyester staple fibers obtained in Examples 1 to 3 were tested respectively. The test results are shown in Table 1;
[0067] Table 1
[0068] Test groups Breaking strength (cN / dtex) Moisture regain (%) Example 1 4.9 1.9 Example 2 4.6 1.7 Example 3 4.8 1.8
[0069] According to Table 1, the breaking strength and moisture regain of the polyester staple fibers obtained in Examples 1 to 3 all meet the standard requirements.
[0070] 2. The polyester staple fibers obtained in Examples 1 to 3 were spun into fabrics respectively, and then far-infrared performance tests were performed respectively. The test results are shown in Table 2.
[0071] Table 2
[0072] Test groups Normal emissivity Standard requirements for normal emissivity in conclusion Example 1 0.98 ≥0.80 qualified Example 2 0.97 ≥0.80 qualified Example 3 0.96 ≥0.80 qualified
[0073] According to Table 2, the normal emissivity of the fabrics spun from polyester staple fibers obtained in Examples 1 to 3 is greater than the standard requirement and has a warm-keeping function.
[0074] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing polyester staple fibers, comprising the following steps: Step 1: heating the fiber of coconut shell to 1200° C., carbonizing it under vacuum, and ultrafine grinding the carbonized fiber to obtain ultrafine coconut charcoal fiber powder, wherein the particle size of the ultrafine coconut charcoal fiber powder is 10 μm; Step 2: Place the coconut charcoal fiber ultrafine powder into the reaction vessel of the atomic deposition equipment at a reaction temperature of 100°C; Step 3: introducing titanium tetraisopropoxide vapor into a continuously stirred reaction vessel for 8 seconds, purging with nitrogen for 20 seconds, and then intermittently introducing deionized water into the reaction vessel for 8 seconds, purging with nitrogen for 20 seconds; Repeat step 3 for 400 times to deposit a 40nm titanium dioxide film on the surface of the coconut charcoal fiber ultrafine powder, making the surface of the coconut charcoal fiber appear purple-red; Step 4: 300 kg of terephthalic acid and 50 kg of organic solvent ethanol or isopropanol are mixed at 50° C.; Then the temperature was raised to 150°C for esterification reaction, and the reaction time was 10 min; Step 5: Add 59.8 kg of carbon fiber ultrafine powder with titanium dioxide film deposited on the surface obtained in step 3 to the product after the esterification reaction; then add 8 kg of dimethyl propanediol, 5 kg of 2,5-dimethyl-2,5-hexyne diol, 5 kg of 2-butene-1,4-di-n-butyl ester, 5 kg of di(hexane-1,6-diol) titanium, 5 kg of composite functional additives, 100 kg of terephthalic acid and 50 kg of ethylene glycol ester, then heat to 200°C, react under 200 Pa vacuum condition for 10 min, and carry out the first polymerization reaction; then add 89. ... propanediol, 5 kg of 2-butene-1,4-di-n-butyl ester, 5 kg of di(hexane-1,6-diol) titanium, 5 kg of composite functional additives, 100 kg of terephthalic acid and 50 kg of ethylene glycol ester, then heat to 200°C, react under 200 Pa vacuum condition for 10 min, and carry out the first polymerization reaction; then add 89.8 kg of dimethyl propanediol, 5 kg of 2,5-dimethyl propanediol, 5 kg of 2-butene- 72kg of the carbon fiber ultrafine powder with a titanium dioxide film deposited on the surface obtained in step 3, reacting for 5 minutes at 230°C and 250Pa vacuum conditions, performing a second polymerization reaction, and obtaining a copolyester melt; the composite functional additive is a mixture of silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder, the mass ratio of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 1:2:1:2, and the particle size of the silicon dioxide, germanium dioxide, aluminum oxide and surface-modified aluminum-doped zinc oxide powder is 10 microns; Step 6: melt-spinning the copolyester melt to obtain a melt, wherein the spinning temperature is 270° C.; Step 7: Extruding the melt through a special-shaped spinneret to form a melt stream, and cooling the melt stream, wherein the spinneret has a spinning micropore in the shape of a gear and has 6 teeth; the cooling comprises: solidifying the melt stream into a filament by a side-blowing cooling process; the side-blowing cooling process comprises: a side-blowing speed of 0.30 m / s-0.50 m / s, a side-blowing temperature of 18° C., and a side-blowing humidity of 75%; Step 8: The melt stream extruded and cooled from the spinneret is subjected to wire guiding, heat setting and winding. Specifically, the filament bundle after oiling and bundling by the nozzle is input into the lower wire guide disk at a speed of 3105 m / min, and then enters the hot wire guide roller at a speed of 3105 m / min and a temperature of 120°C for heat setting; the winding is carried out at a winding speed of 3100 m / min to obtain the polyester staple fiber; and the polyester staple fiber is obtained.
